2022
DOI: 10.1002/pds.5437
|View full text |Cite
|
Sign up to set email alerts
|

How measurements affected by medication use are reported and handled in observational research: A literature review

Abstract: In epidemiological research, measurements affected by medication, for example, blood pressure lowered by antihypertensives, are common. Different ways of handling medication are required depending on the research questions and whether the affected measurement is the exposure, the outcome, or a confounder.This study aimed to review handling of medication use in observational research.Methods: PubMed was searched for etiological studies published between 2015 and 2019 in 15 high-ranked journals from cardiology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…9 As practical guidance, several authors 4,[10][11][12] discussed statistical methods that could be used when measurements are affected by medication use. However, our recent review of the handling of medication use in medical papers 13 demonstrated that a majority of studies featured vaguely formulated research questions and unclear research aims. Invalid methods were often used and a justification for the chosen method was rarely given.…”
Section: Introductionmentioning
confidence: 99%
“…9 As practical guidance, several authors 4,[10][11][12] discussed statistical methods that could be used when measurements are affected by medication use. However, our recent review of the handling of medication use in medical papers 13 demonstrated that a majority of studies featured vaguely formulated research questions and unclear research aims. Invalid methods were often used and a justification for the chosen method was rarely given.…”
Section: Introductionmentioning
confidence: 99%